Flood-Irrigated Soybean Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2003)
This publication projects a budget that reflects expected income and costs based on flood-irrigated soybean production in western Kansas.
MF577_2003_10
Keywords: MF577; Economics; Crops; MF